Affordable Rental Housing : Making It Part of Europe's Recovery - ElFayoumi, Khalid (Departmental Papers; Departmental Paper ;, 2021)
Many European economies have faced pressure from rental housing affordability that has widened social and economic divergence. While significant country and regional differences exist, this departmental paper finds that in many advanced European economies a large and rising share of low-income renters, the young, and those living in cities is overburdened. In several locations, middle-income groups also increasingly face rental affordability issues.